Self-Assembled Lipoplexes of Short Interfering RNA (siRNA) Using Spermine-Based Fatty Acid Amide Guanidines: Effect on Gene Silencing Efficiency - Abdelkader A. Metwally; Ian S. Blagbrough (MDPI AG, 2011)
Four guanidine derivatives of N4,N9-diacylated spermine have been designed, synthesized, and characterized. These guanidine-containing cationic lipids bound siRNA and formed nanoparticles. Two cationic lipids with C18 unsaturated chains, N1,N12-diamidino-N4,N9-dioleoylspermine and N1,N12-diamidino-N4-linoleoyl-N9-oleoylspermine, were more efficient in terms of GFP expression reduction compared to the other cationic lipids with shorter C12 (12:0) and very long C22 (22:1) chains. N1,N12-Diamidino-N4-linoleoyl-N9-oleoylspermine siRNA lipoplexes resulted in GFP reduction (26%) in the presence of serum, and cell viability (64%). These data are comparable to those obtained with TransIT TKO. Thus, cationic lipid guanidines based on N4,N9-diacylated spermines are good candidates for non-viral delivery of siRNA to HeLa cells using self-assembled lipoplexes.